Design 60-ghz band antenna for 5G communication system - Nur Naimah, Hasbullah (2021)
Radio frequency (RF) energy harvesters are an emerging and much promising technology that offers a new way to power low consumption devices. The investigation of the power capabilities of an energy harvester is essential, and for this reason, a simulation tool of an energy harvester is introduced. This paper presents the design of a microstrip patch antenna, a bandpass filter and a rectifier for 5G wireless application operating at 60GHz. The antenna is design and simulated and the analysis were carried out on High Frequency Structure Simulator (HFSS). Meanwhile The bandpass filter and rectifier are design and simulated and the analysis were carried out on Advanced Design System (ADS) software. The simulation results show that the proposed circuit able to produce approaching 2V DC output voltage at frequency at 60GHz with an input power of 200mW. This paper also presents the development of RF energy harvesting via combining all the component for 5G wireless application operating at 60GHz band frequency. The physical model comprises of antenna, a band- pass filter, a matching microstrip line, and a Schottky diode are designed using lumped components was designed and developed using the software High Frequency Structure Simulator (HFSS) and Advanced Design System (ADS). ADS software for designing microwave electronic circuits. Schottky diode and capacitors is used for rectification. The energy harvesting via environmental source. In theory, it can produce multiple outputs from the input power supply, depending on the stage used. The higher the frequency, the higher the output that can be produced. In addition, the amount of frequency can be obtained based on the size and range of the frequency.